For the Moment, I Am Not Scrolling - Andrew Culp; Claudia Skinner; Adi Kuntsman; Esperanza Miyake; Tero Karppi (Lateral, 2023)
Andrew Culp and Cultural Studies Association's New Media and Digital Cultures Working Group Co-Chair Claudia Skinner take a look into Adi Kuntsman and Esperanza Miyake’s new book Paradoxes of Digital Disengagement: In Search of the Opt-Out Button, published by University of Westminster Press (2022). This podcast is accompanied by a scholarly commentary by Tero Karppi.